Prizes, Publicity and Patents: Non‐Monetary Awards as a Mechanism to Encourage Innovation1. (21st October 2013) - Moser, Petra; Nicholas, Tom
Abstract : This paper exploits the selection of prize‐winning technologies among exhibitors at the Crystal Palace Exhibition in 1851 to examine whether—and how— ex post prizes that are awarded to high‐quality innovations may encourage future innovation. U.S. patent data indicate a 40 per cent increase after 1851 in patenting for prize‐winners compared with other exhibits. Results are robust to controlling for technology‐specific pre‐trends and for the quality of patents. A comparison of changes in patenting for prize‐winners with changes for technologies that were described on the front page of the Scientific American suggests that publicity for promising research fields may be an important mechanism by which ex post prizes encourage future innovation.